Elovl3: a model gene to dissect homeostatic links between the circadian clock and nutrition status - Anzulovich Miranda, Ana Cecilia (2006)
The ELOVL3 protein is a very long-chain fatty acid elongase found in liver, skin, and brown adipose tissues. Circadian expression of the Elovl3 gene in the liver is perturbed in mutant CLOCK mice but persists in mice with severe hepatic dysfunction. A reliance on an intact clock, combined with the refractoriness to liver decompensation and the finding of a robust sexually dimorphic pattern of expression, evince a particularly complex mode of transcriptional control. The Elovl3 gene upstream region was repressed by RevErbα and activated by sterol-regulatory element binding protein-1 (SREBP1) transcription factors. We propose that the temporal coordination of RevErbα and SREBP1 activities integrates clock and nutrition signals to drive a subset of oscillatory transcripts in the liver. Proteolytic activation of SREBP1 is circadian in the liver, and because the cycle of SREBP1 activation was reversed after restricting meals to the inactive phase of the day, this factor could serve as an acute sensor of nutritional state. SREBP1 regulates many known lipogenic and cholesterogenic circadian genes; hence, our results could explain how feeding can override brain-derived entraining signals in the liver. This mechanism would permit a rapid adjustment in the sequence of key aspects of the absorptive and postabsorptive phases in the liver.